Codex Cumanicus. История изучения - Стоянов, Г. (Материалы по археологии, истории и этнографии Таврии, 2003)
Исследование Codex Cumanicus многими известными филологами и историками длится около двух веков. Его публикация дала возможность ознакомиться с ценным источником, обогатившим наши знания о взаимоотношениях Залада и Востока в далеком XIV столетии. Кроме того, она положила начало научному изучению куманского этноса. In historiographic article the characteristic of a valuable source is given. It enriched our knowledge about interrelationships between the West and the East in the 14th century. Many philologists and historians have been researching Codex Cumanicus for about two centuries. Having examined the results of more than 150 specific publications about this monument it became obvious that the interest of the researchers is directed to the problems of structure, contents and composition, dating and origin, its authors and its function, as weli as the problem if it is the original or a copy or a copy of a copy. Special attention is paid to religious texts, Cumanic riddles and calendar, to numerous linguistic data that show the importance of the source in linguistic and culture-historic aspects.